An integration of net imported emissions into climate change targets. Issue 52 (October 2015) - Scott, Kate; Barrett, John
Highlights: Well established global decarbonisation scenarios are extended to include trade. UK territorial climate targets underestimate its contribution to global emissions. Up to 55% of cumulative UK consumption emissions to 2050 could be emitted abroad. A consumption perspective offers additional emissions reduction opportunities. Abstract: There is an international divide between net emissions importers and net emissions exporters, with industrialised nations mainly falling into the former and emerging economies the latter. Integrating emissions transfers into climate policy, so as not to disadvantage export-intensive countries, has been suggested to increase participation in international emissions reduction commitments. Consumption-based scenarios are presented for the UK identifying the geographic and sectorial source of emissions to meet future consumer demands given the current international climate policy landscape. The analysis is applied to the UK yet the discussion is applicable to international climate policy; assigning national responsibility for global emissions reductions; and extending the mitigation potential for net importing countries. Two trajectories for UK consumption emissions are calculated in which (1) international reduction targets are consistent with those pledged today equating to four degrees of temperature rise and (2) international reduction targets achieve a two degree future. By 2050 it is estimated that UK consumption emissions are 40–260% greater than UK territorial emissions depending on the strength of global reduction measures, and assuming the UK meets its 80% reduction in 1990 emissions by 2050 target. Cumulative emissions are presented alongside emissions trajectories, recognising that temperature rise is directly related to every tonne of carbon emitted. Whilst this paper argues that the current UK emissions targets underestimate the UK's contribution to global mitigation for two degrees, it shows how expanding the focus of policy towards consumption introduces new opportunities for reduction strategies at scale. The paper advocates the implementation of consumption-based emissions accounting which reveals underexploited policy interventions and increases the potential to break down barriers that exist between industrialised and emerging economies in international climate policy.